HIV risks and needs related to the Sustainable Development Goals among female sex workers who were commercially sexually exploited as children in Lesotho. (27th February 2018) - Grosso, Ashley; Busch, Shianne; Mothopeng, Tampose; Sweitzer, Stephanie; Nkonyana, John; Mpooa, Nkomile; Taruberekera, Noah; Baral, Stefan
Abstract: Introduction: Sustainable Development Goals (SDGs) about gender equality; decent work; and peace, justice, and strong institutions include a focus on eradicating trafficking and sexual exploitation of and violence against women and children. In Lesotho, 86% of women have experienced gender‐based violence. In addition, overall HIV prevalence is among the highest globally, and higher among adolescent girls than boys. Moreover, nearly three quarters of female sex workers (FSW) are estimated to be living with HIV in Lesotho. In this context, sexually exploited children may be particularly vulnerable to violence and HIV acquisition risks. This study's objective is to examine the prevalence and correlates of experiencing sexual exploitation as a child among FSW in Lesotho. Methods: FSW (≥18 years) recruited through respondent‐driven sampling in Maseru and Maputsoe from February to September 2014 completed HIV and syphilis testing and an interviewer‐administered survey, including a question about the age at which they started providing sex for money. This study examined correlates of experiencing sexual exploitation as a child (<18 years) through multivariable logistic regression analyses for each city, controlling for current age. Results: Across both cities, 20.0% (142/710) of participants were sexually exploited as children. Among them, 65.5% (93/142) tested positive for HIV and 31.0% (44/142) for syphilis, which was similar to those who started selling sex as adults, after adjusting for current age. Participants who experienced child sexual exploitation were more likely to have been forced to have sex before age 18 than those who started selling sex as adults (Maseru‐adjusted odds ratio (aOR): 3.52, 95% Confidence Interval (CI): 1.61 to 7.66, p  = 0.002; Maputsoe‐aOR: 4.39, 95% CI: 1.22 to 15.75, p  =   0.023). In Maseru, participants who were sexually exploited as children were more likely to avoid carrying condoms to prevent trouble with police (aOR: 3.18, 95% CI: 1.50 to 6.75, p  =   0.003). Conclusions: Risk determinants for HIV and violence among sexually exploited children can be studied retrospectively through research with adult FSW. Further research working directly with sexually exploited children will improve understanding of their needs. Preventing commercial sexual exploitation of children and addressing the social and healthcare needs of those who are exploited are necessary to fully achieve SDGs 5, 8 and 16 and an AIDS‐Free Generation.